2008
DOI: 10.1007/s00018-008-7516-5
|View full text |Cite
|
Sign up to set email alerts
|

The roles of poly(ADP-ribose)-metabolizing enzymes in alkylation-induced cell death

Abstract: Abstract. Poly(ADP-ribose) (PAR) has been identified as a DNA damage-inducible cell death signal upstream of apoptosis-inducing factor (AIF). PAR causes the translocation of AIF from mitochondria to the nucleus and triggers cell death. In living cells, PAR molecules are subject to dynamic changes pending on internal and external stress factors. Using RNA interference (RNAi), we determined the roles of poly(ADP-ribose) polymerases-1 and -2 (PARP-1, PARP-2) and poly(ADP-ribose) glycohydrolase (PARG), the key enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 39 publications
(50 reference statements)
2
51
0
Order By: Relevance
“…Suckau et al (24) reported on targeted RNAi for the treatment of heart failure. Cohausz et al (25) found that PARP-1 siRNA could down-regulated PARP-1 protein expression, it was confirmed by immunofluorescence. Our data indicate that high glucose up-regulated PARP-1 mRNA and protein expression in HPMCs, and PARP-1 siRNA may partly inhibit PARP-1 expession.…”
Section: Discussionmentioning
confidence: 80%
“…Suckau et al (24) reported on targeted RNAi for the treatment of heart failure. Cohausz et al (25) found that PARP-1 siRNA could down-regulated PARP-1 protein expression, it was confirmed by immunofluorescence. Our data indicate that high glucose up-regulated PARP-1 mRNA and protein expression in HPMCs, and PARP-1 siRNA may partly inhibit PARP-1 expession.…”
Section: Discussionmentioning
confidence: 80%
“…To conduct a direct assessment of the potential relationship between PARP and minocycline in a lung injury setting, we examined whether treatment with minocycline blocked PARP activation mediated by the potent DNA alkylating agent MNNG (27,28). Mice, pretreated with the same dose of minocycline used to achieve the anti-inflammatory effects described above, received an intratracheal administration of 10 mg/kg MNNG and were sacrificed 1 h later.…”
Section: Lack Of An Association Between Minocycline-mediated Reductiomentioning
confidence: 99%
“…Small interfering RNAs (siRNAs) against Becn1 (siRNA-B1; 5=-AAAGCUA CCAUUGCAUGGUCA-3= [antisense sequence]), Parp1 (siRNA-P1; 5=-AAGAGCGATGCCTATTACTGC-3= [antisense]) (7), Parp2 (siRNA-P2; 5=-AAGATGATGCCAGAGGAACTC-3= [antisense]) (7), and Trpm2 (siRNA-T2; 5=-UACUCGACCACGUAGACUCCA-3= [antisense]) (3) were obtained from Applied Biosystems. For maximal silencing efficacy, we performed silencing of Becn1 for 24 h and that of all others for 72 h. H 2 O 2 treatment.…”
Section: Cell Culture Immortalized Mefs From the Parp1 ϩ/ϩ (Wild Typmentioning
confidence: 99%